Sovereign Between Homogeneity and the Social Diversity - Discourse on the Ideas of J. S. Mill - Kalemaj, Eriseld (European Journal of Multidisciplinary Studies, 2016)
In the context of political philosophy, one main issue that needs to be discussed is the notion of “sovereign”. The focus will be on the debate created following Rousseau’s theory and the French Revolution. In this article, we pay attention to the philosophical controversial that the famous English philosopher J. S. Mill (1806 – 1873) displays as a well-known author of utilitarianism and as a precursor of liberalism. This discourse rises above the trend to deduce society and in this logic, it is justified the sovereign as an embodiment of unity on one hand, and on the other one, it is the action on the dynamic condition of society or the problem of individual freedom. The question that rises here is on how legitimate will be the political power in a comprehensive decision if it will violate the freedom of just one of the subjects of society. Thus, the efforts should be oriented to the way the political power is brought which will create a particular culture on doing politics. In this sense we should ask about the profile that a sovereign should have. Trying to understand this kind of profile, we should see the sovereign in a “triangle” of factors, such as: the community (custom or public opinion); the power (objective representative of society); and freedom of the individual (the moral subject).